Proses Penciptaan Karya Seni Ngarumat - Wijaya, Cecep (PANGGUNG, 2014)
ÃÂ This paper is a part of theses in graduate programs at Indonesian Arts Institute (ISI) in Sura- karta. Music composition under cultivation is titled Ã¢â¬ÅngarumatÃ¢â¬Â that has inspired from ritual Hajat Buruan, which was in a Bandung suburban that has been a tradition carried out by the local commu- nity. Methods used in the process of creating this work of art is an experiment and exploration. The Tradition of ritual Hajat Buruan is still maintained and always served as a means of cultural ritual jargon: ngajaga lembur, akur jeung batur, panceg dina galur, which means: keep the area together with obey the rules that applied.ÃÂ Keywords: tradition, music compotitionÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Tulisan ini merupakan bagian dari tesis di program pascasarjana di Institut Seni Indo- nesia (ISI) Surakarta. Komposisi musik yang digarap berjudul Ã¢â¬ËngarumatÃ¢â¬â¢ yang terinspirasi dari ritual Hajat Buruan, yang berada di pinggiran kota Bandung yang telah menjadi tradisi yang dilakukan oleh masyarakat setempat. Metode yang digunakan dalam proses pencip- taan karya seni ini adalah eksperimen dan eksplorasi. Tradisi ritual Hajat Buruan masih di- pertahankan dan selalu disajikan sebagai sarana jargon ritual budaya: ngajaga lembur, akur jeung batur, panceg dina galur, yang artinya: menjaga daerah bersama-sama taat pada aturan yang ada.ÃÂ Kata kunci: tradisi, komposisi musik